1975
DOI: 10.1172/jci108136
|View full text |Cite
|
Sign up to set email alerts
|

The role of iron in the pathogenesis of porphyria cutanea tarda. II. Inhibition of uroporphyrinogen decarboxylase.

Abstract: A B S T R A C T Porphyria cutanea tarda is characterized biochemically by excessive hepatic synthesis and urinary excretion of uroporphyrin I and 7-carboxyl porphyrins. This pattern of excretion suggests an impaired ability to decarboxylate uroporphyrinogen to the 4-carboxyl porphyrinogen, coproporphyrinogen, a reaction catalyzed by the enzyme uroporphyrinogen de-carboxylase.Because clinical evidence has implicated iron in the pathogenesis of porphyria cutanea tarda, these experiments were designed to study th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0
2

Year Published

1976
1976
2003
2003

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(50 citation statements)
references
References 18 publications
5
43
0
2
Order By: Relevance
“…We have reported that iron, an inhibitor of URODECARB, exerts its major inhibitory effect upon the removal of the second carboxyl group, leading to the accumulation of uroporphyrin and 7-carboxyl porphyrin in an in vitro hepatic model of PCT (25). Histologic evidence of excessive hepatocellular iron was found in specimens from all of the patients studied here, a finding that is virtually uniform in PCT (16).…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…We have reported that iron, an inhibitor of URODECARB, exerts its major inhibitory effect upon the removal of the second carboxyl group, leading to the accumulation of uroporphyrin and 7-carboxyl porphyrin in an in vitro hepatic model of PCT (25). Histologic evidence of excessive hepatocellular iron was found in specimens from all of the patients studied here, a finding that is virtually uniform in PCT (16).…”
Section: Introductionmentioning
confidence: 56%
“…The concept that there may be a genetically determined contribution to the pathogenesis of PCT has been strengthened by occasional reports describing a familial occurrence of the disease (19,20). In addition, several reports have described abnormalities of porphyrin metabolism in apparently unaffected relatives of patients with PCT (21,22 URODECARB was assayed by a previously published method by utilizing enzymatically generated, tritiated uroporphyrinogen as the substrate and thin layer chromatographic identification and liquid scintillation quantitation of the reaction products (25).…”
Section: Introductionmentioning
confidence: 99%
“…Turnbull et al [131] and Reizenstein et al [132] reported increased iron absorption in overt PCT and this was found also in the presence of excess liver iron. As to the relationship between decreased uroporphyrinogen decarboxylase activity and excess liver iron, most studies suggest an inverse relationship between enzyme activity and liver iron [133][134][135] although Blekkenhorst et al [136] claimed that ferrous iron enhances uroporphyrinogen decarboxylase activity. According to Elder & Sheppard [1371, in PCT there is loss of enzyme activity but no loss of enzyme protein.…”
Section: Transferrin and Alcoholic Liver Diseasementioning
confidence: 99%
“…Decreases in this heme pool may arise as the result of enhanced heme breakdown or of decreased heme synthesis. It has been proposed by some investigators that iron decreases hepatic heme synthesis by inhibiting uroporphyrinogen decarboxylase (6). However, others have reported no effect (7) or activation (8) of the decarboxylase by ionic iron.…”
Section: Introductionmentioning
confidence: 99%